Iron fists : branding the 20th-century totalitarian state - Heller, Steven 1950- (Phaidon Press, 2008)
Totalitarianism and art ; Propaganda, Communist -- Soviet Union ; Propaganda, Communist -- China ; Nazi propaganda ; Fascist propaganda -- Italy ; Political posters . Grafikdesign, Kommunikationsgestaltung, Plakat, Plakatgestaltung - Totalitäre Systeme, Diktatur, Propoganda